Synthesis of silver nanoparticles using gum Arabic: Evaluation of its inhibitory action on Streptococcus mutans causing dental caries and endocarditis - Mysoon M. Al-Ansari; Nora D. Al-Dahmash; A.J.A. Ranjitsingh (Elsevier, 2021)
Background: Streptococcus mutans are an oral pathogen that causes dental caries, endocarditis, and systemic dysfunctions, an alternative antibacterial solution from silver nanoparticles (AgNPs) are investigated. Methods: AgNPs were synthesized using the ethnobotanical product gum Arabic. It influenced the nanoparticles with medicinal value through their role as capping, stabilizing, or surface-attached components. The biophysical characteristics of the synthesized AgNPs were studied using UV-vis spectrum, XRD, EDAX, SEM, and TEM tools. The AgNPs were spherical with the average size less than 10 nm. By using the well diffusion and microdilution techniques, the impact of synthesized AgNPs was tested against S. mutans isolates. Results: The smaller the size, the greater the antibacterial and antiviral potential the particles exhibit. The biophysical characteristics of AgNPs the presence of phenols, alcohols, amides, sulfoxide, flavanoids, terpenoids and steroids. The AgNPs exhibited a good antibacterial action against the oral pathogen S. mutans. The synthesized NPs at a dose level of 200 μg/mL exhibited an inhibition zone with 18.30 ± 0.5 nm diameter. The synthesised nanoparticles inhibited the genes responsible for biofilm formation of S. mutans over host tooth and gums (gtfB, gtfc, gtfD) and virulent protective factors (comDE, brpA and smu 360) and survival promoter genes (gyrA and spaP, gbpB). Conclusion: The potent antibiotic action over S. mutans seen with the synthesized NPs, paves the way for the development of novel dental care products. Also, the small-sized NPs promote its applicability in COVID-19 pandemic containment.